COPRODUCTION FOR SUSTAINABILITY: SEEKING THE PERSPECTIVES OF INFORMAL DEMENTIA CARERS' ON CAPACITY BUILDING FOR COMMUNITY SERVICES. Issue 2 (March 2017) - Elliott, Kate‐Ellen J.; Stirling, Christine M.; Martin, Angela J.; Robinson, Andrew L.; Scott, Jennifer L.
Abstract : Dementia is a worldwide health priority and much of the burden of care for people with dementia is placed on family members and informal systems of care in the community. The perspectives of 36 informal dementia carers on current and future community‐based services for people with dementia in Tasmania, Australia, are reported using a mixed methods design. Qualitative data were collected, thematically analyzed, and double coded. Quantitative data were collected and analyzed to determine carers' level of satisfaction with services. Three main themes were identified: (a) quality support for carers and people with dementia; (b) adaptive, tailored, and flexible organizations; and (c) development of the workforce. Although most carers were highly satisfied with the current support services they received, they wanted organizational and workforce changes to meet their varied and complex needs. Results suggest a community‐driven agenda for a coproduction approach for aged and dementia care reform in Australia.